2014
DOI: 10.1016/j.aquatox.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Similar anxiolytic effects of agonists targeting serotonin 5-HT1A or cannabinoid CB receptors on zebrafish behavior in novel environments

Abstract: The discovery that selective serotonin reuptake inhibitors (SSRIs) such as fluoxetine are present and bioaccumulate in aquatic ecosystems have spurred studies of fish serotonin transporters (SERTs) and changes in SSRI-sensitive behaviors as adverse outcomes relevant for risk assessment. Many SSRIs also act at serotonin 5-HT1A receptors. Since capitolizing on this action may improve treatments of clinical depression and other psychiatric disorders, novel multimodal drugs that agonize 5-HT1A and block SERT were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 87 publications
2
48
0
Order By: Relevance
“…Prior studies have employed immersion-based drug delivery with zebrafish using DMSO. The concentration of DMSO employed in these studies reached 0.4 % (vol/vol) with no significant effects on the behaviour of zebrafish larvae (Irons et al 2013;Giacomini et al 2006) and 0.1 % in adult zebrafish (Connors, et al 2014).…”
Section: Drug Administrationmentioning
confidence: 99%
“…Prior studies have employed immersion-based drug delivery with zebrafish using DMSO. The concentration of DMSO employed in these studies reached 0.4 % (vol/vol) with no significant effects on the behaviour of zebrafish larvae (Irons et al 2013;Giacomini et al 2006) and 0.1 % in adult zebrafish (Connors, et al 2014).…”
Section: Drug Administrationmentioning
confidence: 99%
“…Immersion-based drug delivery was used because of its less invasive nature compared to other methods of administration (e.g. injection) and frequent use in adult zebrafish research (Nowicki et al, 2014; Tran et al, 2015b; Levin et al, 2007; Conners et al, 2014; Sackerman et al, 2010). …”
Section: Methodsmentioning
confidence: 99%
“…A radiolabeled version of the sCB WIN55212-2 has been shown to bind to targets throughout the hypothalamus, optic tectum, and telencephalon in adult zebrafish brain slices (Connors et al, 2014). Similarly, binding assays have confirmed that the eCB AEA, and the sCBs HU-210, WIN55212-2, and CP55940 interact with receptors in adult brain homogenates (Rodriguez-Martin et al, 2007b).…”
Section: Zebrafish Ecb Gene Functionmentioning
confidence: 99%
“…Exposure to 1 mg/L WIN55212-2 was shown to increase shoaling behavior, thereby demonstrating anxiolytic effects in this visual-social interaction test. Subsequently, Connors et al investigated the potential anxiolytic effects of WIN55212-2 on zebrafish behavior using an aquatic light-dark plus maze test (Connors et al, 2014). In this paradigm, dietary exposure to 1 μg/day WIN55212-2 significantly decreased the latency to enter the light arms and increased the time spent dwelling in them.…”
Section: Zebrafish Ecb Gene Functionmentioning
confidence: 99%